Electric field-induced ultrahigh strain and large piezoelectric effect in Bi1/2Na1/2TiO3-based lead-free piezoceramics. Issue 3 (February 2016) - Cheng, Renfei; Xu, Zhijun; Chu, Ruiqing; Hao, Jigong; Du, Juan; Li, Guorong
Abstract: Lead-free piezoelectric ceramics, (Bi1/2 Na1/2 )0.935 Ba0.065 Ti1− x (Fe1/2 Nb1/2 ) x O3, were prepared by the conventional solid-state reaction method. The room temperature ferroelectric P–E loops illustrated the transition of ferroelectric domains. The composition and electric field dependent strain behavior of this system were investigated. A highest unipolar strain of ∼0.422% and corresponding normalized strain, d * 33 ( =  S max / E max ) of 844 pm/V under an applied field of 50 kV/cm were observed at x  = 0.020, due to the destabilization of the ferroelectric order. It is observed that the unipolar strain of BNBT-0.02FN is temperature insensitive, and the d * 33 maintains a high value of ∼600 pm/V at 90 °C. The observed large strain behavior can be attributed to the transformation from the ferroelectric phase at zero electric field into a relaxor ferroelectric phase under an applied electric field. The large strain response with good temperature stability would be quite suitable for environmental-friendly solid-state actuator applications.